(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Research, laboratory-based or clinical, is essential for development of all countries. Magnetic resonance spectroscopy (MRS) analyses small particles and is related to magnetic resonance imaging of humans. Dengue fever is an infectious disease of humans. Objective This investigation is based on the idea to study the role of MRS and opportunities to use the internet for clinical support in the low-income country Cambodia. Methods The biomedical research database PubMed was employed to quantify number of publications of MRS and dengue fever research in Laos, Cambodia, Vietnam, Thailand, Japan and United States of America (USA). Gross domestic product (GDP) and dengue fever case numbers were obtained from reference resources. Correlation analysis was used. Results 4 MRS research publications were identified for Cambodia (minimum 0 for Laos and maximum 42602 for USA). Cambodia had a GDP of 29.96 billion USD (minimum Laos 19 billion USD and maximum USA 25462.7 billion USD).The correlation coefficient between MRS research publications and GDP was 0.9727.Cambodia had 9, Laos 0, Vietnam 16 and USA 106 dengue fever research publications. Cambodia had 12500, Laos 32364, Vietnam 361813 and USA 1188 dengue fever cases. The correlation coefficient between Dengue fever research publications and Dengue fever cases was -0.2022. Conclusion MRS research in Cambodia is limited. MRS research in the investigated countries in Asia and USA is related to country GDP and wealth.High numbers of country Dengue fever cases did not predict a high number of Dengue fever research publications in the studied countries. Pubmed can guide medical doctors in lowincome countries with research planning of infectious diseases and other clinical questions. BJMS, Vol. 25 No. 02 April’26 Page: 526-531